2016
DOI: 10.1093/annonc/mdw265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nivolumab on health-related quality of life in patients with treatment-naïve advanced melanoma: results from the phase III CheckMate 066 study

Abstract: In patients with advanced melanoma in the CheckMate 066 study, baseline health-related quality of life (HRQoL) with nivolumab was maintained over time, with statistically significant and clinically meaningful improvements in some exploratory analyses, and no HRQoL improvements with dacarbazine. Added to the survival benefit of nivolumab, the benefit-to-risk ratio favors nivolumab over dacarbazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 18 publications
1
81
0
5
Order By: Relevance
“…Patients treated with pembrolizumab had consistently smaller decrements in the symptoms scales for fatigue, nausea, anorexia, diarrhea, and constipation. Recently, Long et al reported PRO outcomes in the trial of nivolumab versus dacarbazine in patients with advanced melanoma . The EORTC QLQ‐C30 was evaluated at baseline and every 6 weeks while on treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with pembrolizumab had consistently smaller decrements in the symptoms scales for fatigue, nausea, anorexia, diarrhea, and constipation. Recently, Long et al reported PRO outcomes in the trial of nivolumab versus dacarbazine in patients with advanced melanoma . The EORTC QLQ‐C30 was evaluated at baseline and every 6 weeks while on treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported outcomes in a trial comparing placebo with high-dose adjuvant ipilimumab suggest a lesser, more transient effect on neurocognitive function 23 . Results from the use of anti-PD-1 agents in the metastatic setting suggest a favourable effect on quality of life 24,25 . Serious mental health or constitutional symptoms directly attributable to treatment appear to be rare 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life for nivolumab has been assessed in the Checkmate 066 study comparing nivolumab and chemotherapy at first line setting. Patients on nivolumab maintained baseline quality of life as measured by the Euroquality of Life Five Dimensions for longer time and did not show increased symptom burden as assessed by the QLQ-C30 (15).…”
Section: Latest Advances In Anti-pd-1/pd-l1 Antibodies Developmentmentioning
confidence: 95%